Small subunit M20 augments inhibitory phosphorylation of MYPT1 in myosin light chain phosphatase by inhibiting autodephosphorylation - Tetsuo Yamashita; Noriyuki Kodera; Masumi Eto; Risa Omura; Mayumi Hirano; Takeshi Hashimoto; Katsuya Hirano (Proceedings of the National Academy of Sciences, 2026)
Smooth muscle myosin light chain phosphatase (MLCP), composed of a catalytic subunit PP1c and large and small noncatalytic subunits (MYPT1 and M20, respectively), is a key mediator of Rho-associated coiled-coil-containing kinase (RhoA-ROCK) signaling in cytoskeletal regulation. Phosphorylation of MYPT1 at Thr696 and Thr853 inhibits MLCP activity and augments MLC phosphorylation and smooth muscle contraction, whereas the functions of M20 remain undefined. To elucidate the functional significance of M20 in MLCP regulation, the present study compared the biochemical and structural properties of recombinant MLCP trimer (PP1c, MYPT1, and M20) and dimer (PP1c and MYPT1) complexes. While the rate of MYPT1 phosphorylation at Thr696 and Thr853 by ROCK2 in the presence of calyculin A was indistinguishable between the trimer and dimer complexes, the subsequent autodephosphorylation initiated by ROCK2 inhibition was significantly slower in the trimer. In the absence of calyculin A, phosphorylation in the trimer was greater than in the dimer. A dimer containing C-terminally truncated MYPT1 (Δ931 to 1030) mimicked trimer properties. Pull-down assays demonstrated the interactions of MYPT1–M20 and MYPT1–MYPT1, which were abolished by MYPT1 (Δ931 to 1030). High-speed atomic force microscopy revealed a superdimer complex consisting of two MLCP dimers tethered to the C-terminal region, whereas the trimer retained a single entity. These findings reveal a function of M20 that augments the inhibitory phosphorylation of MYPT1 by preventing superdimer formation mediated by the C-terminal region of MYPT1 and suppressing autodephosphorylation. Knockdown of M20 decreased the basal phosphorylation of MYPT1. M20 thus maintains MLCP in the inhibited state at basal conditions.